Depth of Penetration and Antimicrobial Activity of 5% and 10% Bamboo Salt, 2% Chlorhexidine Gel and Calcium Hydroxide Against Enterococcus faecalis – An In Vitro Study - Kumar, Palmoor Santosh (European endodontic journal, 2021)
E. faecalis is one of the most commonly found species in persistent and secondary infections associated with endodontic failure. This in vitro study aimed to evaluate the depth of penetration and antimicrobial efficacy of 5% and 10% bamboo salt (BS), 2% chlorhexidine gel (CHX) and calcium hydroxide (CH) against E. faecalis. E. faecalis was inoculated in dentine blocks for 21 days following which the antibacterial efficacy of the experimental medicaments were quantatively assessed by harvesting the dentinal debris from depths of 200 µm and 400 µm from the block lumen on the 2nd and 7th day. The depth of penetration of the medicaments was measured using LIVE/DEAD BacLight stain under CLSM. Results showed that the medicaments had varying degrees of antimicrobial efficacy and depth of penetration. Among the medicaments, CHX showed the highest antimicrobial activity on both the time intervals (P<0.05), followed by 10% BS, 5% BS and the least efficacy was observed in CH group. CHX and 10% BS exhibited the highest depth of penetration, which was proximate to the penetration of E. faecalis. It can be concluded that 10% bamboo salt can serve as a viable natural antimicrobial in endodontic therapy.